GCMs‐based spatiotemporal evolution of climate extremes during the 21st century in China. Issue 19 (15th October 2013) - Li, Jianfeng; Zhang, Qiang; Chen, Yongqin David; Singh, Vijay P.
Abstract [1] Changes in the hydrological cycle being caused by human‐induced global warming are triggering variations in observed spatiotemporal distributions of precipitation and temperature extremes, and hence in droughts and floods across China. Evaluation of future climate extremes based on General Circulation Models (GCMs) outputs will be of great importance in scientific management of water resources and agricultural activities. In this study, five precipitation extreme and five temperature extreme indices are defined. This study analyzes daily precipitation and temperature data for 1960–2005 from 529 stations in China and outputs of GCMs from the Coupled Model Intercomparison Project Phase 3 (CMIP3) and Phase 5 (CMIP5). Downscaling methods, based on QQ‐plot and transfer functions, are used to downscale GCMs outputs to the site scale. Performances of GCMs in simulating climate extremes were evaluated using the Taylor diagram. Results showed that: (1) the multimodel CMIP5 ensemble performs the best in simulating observed extreme conditions; (2) precipitation processes are intensifying with increased frequency and intensity across entire China. The southwest China, however, is dominated by lengthening maximum consecutive dry days and also more heavy precipitation extremes; (3) warming processes continue with increasing warm nights, decreasing frost days, and lengthening heat waves during the 21st century; (4) changes in precipitation and temperature extremes exhibit larger changing magnitudes under RCP85 scenario; (5) for the evolution of changes in extremes, in most cases, the spatial pattern keeps the same, even though changing rates vary. In some cases, area with specific changing properties extends or shrinks gradually. The directions of trends may alter during the evolution; and (6) changes under RCP85 become more and more pronounced as time elapses. Under the peak‐and‐decline RCP26, changes in some cases do not decrease correspondingly during 2070–2099 even though the radiative forcing during 2070–2099 is less than during 2040–2069. The increase of radiative forcing triggers considerable regional variations in consecutive dry days, but causes only slight changes in the areal average in China. The results of this study imply higher flood risk across entire China but intensifying droughts in south China in the 21st century, and also more heat‐related losses in east coasts of China.